Implications of Eikenella corrodens in adverse pregnancy outcomes: The role of dental professionals – A narrative review - Ansari, Aishah; Anwarhussain Mulla, Sayem; Bhattacharjee, Minakshi; Joshi, Nilesh; Singh Sachdev, Sanpreet; Joshi, Mridula (Journal of Neonatal Surgery, 2025)
This review elaborates on the mechanisms by which E. corrodens leads to APOs with a special emphasis on the role of dental professionals in their prevention. The analysis is based on open-access articles from PubMed, SCOPUS, WebofScience, and Google Scholar published in the English language without any restriction for the time of publication. A search was performed using the keywords ‘Eikenella corrodens’ and ‘Pregnancy’ to identify relevant open-access articles in PubMed, SCOPUS, WebofScience, and Google Scholar databases with full text available in the English language without any restriction for the time of publication Eikenella corrodens is a commensal bacterium usually found in the upper respiratory tract, mucosal surfaces like gastrointestinal and genitourinary tract as well as in the human dental plaque. The physiological alterations in pregnancy or lesions such as pregnancy-related gingivitis and pyogenic granuloma render the body susceptible to transient bacteremia. The hematogenous spread of E. corrodens is associated with several adverse pregnancy outcomes that lead to high morbidity and mortality rates for mothers as well as neonates.